(3CReI GdYbGQ GdadGMj h ebJQMGJ JShjJgG ef JCeje Gdedc GdNGU Gdi NhUUI Gdedc GdYGe (B/s - (3GdLjdGdj, YLIs ((3GdLRGFQ(B: s (3OGQ GdNdOhfjI(B, s, 2005)
(3GTcGdjI GdYbGQ GdadGMj Gdeedhc ddOhdI aj Xd GdfXGe GdGTJQGcj (B:(3CReI GdYbGQ GdadGMj Gdeedhc ddOhdI h ebJQMGJ SdWI GYGOI GdgjcdI HTGf CReI GdYbGQ GdadGMj , GTcGdjI GdYbGQ GdadGMj Gdeedhc ddOhdI aj Xd GdfXGe GdQCSeGdj (B: (3GSJbdGdjI GdeSJKeQGJ GdadGMjI h GdJYOjd Gdgjcdj ddGSJZdGdGJ GdadGMjI h GfYGT gPg GdGSJZdGdGJs
(3bGFeI GdeQGLY U(B.299(3;agQS GdLOGhd U(B.316s
Keywords: (3GdYbGQGJs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes